When thought suppression backfires: its moderator effect on eating psychopathology - Ferreira, C. (2015)
Ferreira, C., Palmeira, L., Trindade, I. A., & Catarino, F. (2015). When thought suppression backfires: Its moderator effect on eating psychopathology. Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity, 20(3), 355–362. doi: 10.1007/s40519-015-0180-5.